Professional hadoop® solutions - Lublinsky, Boris; Smith, Kevin T; Yakubovich, Alexey (Wiley, 2013)
The go-to guidebook for deploying Big Data solutions with Hadoop Today's enterprise architects need to understand how the Hadoop frameworks and APIs fit together, and how they can be integrated to deliver real-world solutions.